2013
DOI: 10.5455/ijmsph.2013.2.492-500
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study on quality of life among rural elderly population of nothern India

Abstract: Background: Population ageing is a recognized international reality, both in developed and developing countries. The number of elderly in the developing world is increasing due to demographic transition, whereas their condition is deteriorating as a result of fast eroding traditional family system coupled with rapid modernization and urbanization. Current statistics for the elderly gives a prelude to a new set of medical, social and economic problems that could arise if a timely initiative in this direction is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
51
4
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 5 publications
12
51
4
3
Order By: Relevance
“…Charle HN et al found prevalence of diabetes 24% in urban elderly Qadri S et al in rural Haryana, found prevalence of diabetes was 09% which is similar to our rural finding. 13,18,22 On contrary, Yerpude PN et al in rural area of Guntur, found prevalence of diabetes in rural area around 23% which is higher than our rural finding.…”
Section: Discussioncontrasting
confidence: 55%
“…Charle HN et al found prevalence of diabetes 24% in urban elderly Qadri S et al in rural Haryana, found prevalence of diabetes was 09% which is similar to our rural finding. 13,18,22 On contrary, Yerpude PN et al in rural area of Guntur, found prevalence of diabetes in rural area around 23% which is higher than our rural finding.…”
Section: Discussioncontrasting
confidence: 55%
“…1 Studies done in Northern India shows a higher overall score and also better social and interpersonal relationship scores than our study. 2,8 The differences observed in QOL scores among our study and other studies might be due to the difference in pattern of associated factors as QOL would be affected by events of life related to his/her society or community.…”
Section: Discussionmentioning
confidence: 64%
“…1 There is a need to highlight the medical and psychosocial problems that are being faced by the elderly people in India and strategies for bringing about an improvement in their quality of life. 2 Population ageing is a recognized international reality, both in developed and developing countries. The number of elderly in the developing world is increasing due to demographic transition, whereas their condition is deteriorating as a result of fast eroding traditional family system coupled with rapid modernization and urbanization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] A study conducted by Qadri et al, it was found that the QOL was significantly better in the male sex. [7] In another study by Lokare et al, they have found that QOL was significantly better among male elderly. [4] This finding is matched with the finding of a study done by Lahariya et al [5] Male participants scored significantly higher in all domains in the present study than females.…”
Section: Discussionmentioning
confidence: 99%